The Role of market development strategy on the performance of manufacturing small and medium enterprise owners in southwest Nigeria - Oluwaseun, Oladotun Abimbola; Oladele, Kehinde Joseph; Stephen, Ojeka; Oluwafunmilayo, Onayemi Oluwakemi; Akintunde, Akinola Oluseyi; Esitse, Dada Augustina; Izegbuwa, Tongo Nancy (International Journal of Innovative Research and Scientific Studies, 2024)
The manufacturing sector’s performance is crucial to the development of an economy. The ability of small and medium enterprises (SMEs) to plan their growth strategy is instrumental to attain high performance. The fundamental concept used in this study is the Ansoff matrix model. Hence, this study examined the role of market development in the performance of SMEs. 384 copies of questionnaires were distributed among the manufacturing SME owners and managers in Southwest Nigeria of which 361 copies were retrieved and analyzed. Structural Equation Modelling (SEM) was used for the analysis. The results indicated that market development has a significant effect on SME’s performance. The path coefficients of 0.81, 0.76, 0.80 and 0.85 revealed a large degree of relationship between market development and customer satisfaction, market share, profitability and service quality respectively. According to the statistical analysis, market development has a high predictability for service quality (73.5%) followed by profitability (65.3%), market share (58.7%), customer satisfaction (65.8%) and profitability (65.3%). The implications are that when SME owners enter a new market apart from their existing market and can attract more customers to serve, it will in turn increase the satisfaction of their customers and improve their perceived quality leading to an increase in financial returns as well as an increase in the portion of the market that they control. This study recommends that the management of manufacturing SMEs should venture into new geographical areas with the appropriate development of new market segments and the creation of new distribution channels.